O planejamento educacional para alunos público alvo da educação especial do ensino médio integrado - Franco, Ana Beatriz Momesso (2021)
The National Policy on Special Education in the Perspective of Inclusive Education, in 2008, aimed at the school inclusion of Special Education Target Public (PAEE) students in regular education systems, however, the peak of notoriety about inclusion was given with the publication of the Brazilian Inclusion Law (LBI) in 2015, which reinforces LDB 9394/96 in relation to access and permanence of students with disabilities at all levels of education, with this there was an increase in the number of students with disabilities in all stages of basic education, losing strength when reaching high school. With Law nº 12.711 / 2012, known as the Quotas Law and Law nº 13.409 / 2016, which guarantees the reservation of places for people with disabilities in the technical courses of secondary and higher education at federal educational institutions, this percentage regarding the number of enrollments of PAEE students increased considerably, including access to these students in high school, which made it necessary to think of actions that would contribute to the creation of favorable conditions in the teaching and learning process, as well as their permanence in institutions. In this sense, the present study has the general objective of describing and analyzing the teaching planning for Integrated High School PAEE students in a campus of the Federal Institute of Education, Science and Technology of the State of São Paulo (IFSP) and brings as specific objectives: a) identify the bases and partnerships that occur in the planning for these students, b) analyze the existence of individualized planning and which subjects participated in this process and c) evaluate the advances and challenges experienced by the teachers in the common room at the time of planning the education. The research has as a method the qualitative research with a focus on case study, for that it used concepts from the literature about special education in the perspective of inclusive education, professional and technological education and discussions regarding the planning for student PAEE. The data were collected from semi-structured interviews with nine participants, being the NAPNE coordinator and teachers who teach classes to PAEE students; these interviews were interpreted and related to theories that deal with special education from an inclusive perspective and planning, as well as information from the participants in this research. This study was submitted to and approved by the ethics committee of the Federal University of São Carlos (UFSCar) according to opinion nº 3.539.016. This research had its results discussed according to three categories of analysis: The context of the campus and the Support Center for People with Specific Educational Needs (NAPNE); teaching planning strategies and the role of foundations and partnerships in planning, PAEE students who need accessibility. As a result, it was observed that there are signs of planning for PAEE students on the researched campus in Integrated High School, but the same occurs discontinuously and without much support, even so, there were positive aspects of this planning as the various discussions between teachers and the NAPNE and the efforts to carry out a planning that serves everyone and not just PAEE students. In general, this research showed the importance of the partnership between the special educator and the regular classroom teacher, in order to be a guiding proposal for new critical reflections in favor of the education of everyone involved in the general context of education.